Association between cumulative exposure to ideal cardiovascular health and arterial stiffness. (May 2017) - Zheng, Xiaoming; Zhang, Ruiying; Liu, Xiaoxue; Zhao, Haiyan; Liu, Hongmin; Gao, Jingsheng; Wu, Yuntao; Wu, Shouling
Abstract: Background and aims: Ideal cardiovascular health (CVH) is associated with reduced risk of cardiac and cerebral events. Arterial stiffness plays an important role in the progress of cardiac and cerebral events, but it is unclear whether ideal CVH, in particular, cumulative exposure to ideal CVH (cumCVH), is associated with reduced risk of arterial stiffness. We examined the association between cumCVH and arterial stiffness using data from the Kailuan Study. Methods: The study cohort consisted of 20, 355 participants from the Kailuan community-based cohort, whose mean follow-up period was 3.36 years since baseline (visit 3). CumCVH was calculated as the summed average ideal CVH score between two consecutive visits, multiplied by the time between the two consecutive visits in years. Multivariable linear regression model analysis was used to evaluate the relationship between cumCVH and brachial ankle pulse wave velocity (baPWV).Variance inflation factor (VIF) was calculated to diagnose co-linearity between multiple variables. We also used logistic regression to evaluate the association between cumCVH and arterial stiffness by calculating the crude odds ratio (OR) and adjusted OR, with 95% confidence interval (CI). Sensitivity analysis was performed to test the robustness of our findings. Results: The participants were classified into 5 groups according to the quintile of cumCVH exposure levels. Multivariate linear regression analysis showed that cumCVH had a significant inverse linear relationship with baPWV (B = −3.35, p  < 0.001). The result of logistic regression demonstrated that compared with Q1 group, Q3, Q4, Q5 were associated with a 15%, 24%, 36% significantly lower incidence of arterial stiffness, after adjusting for confounders.What is more, the results of sensitivity analysis had no influence on our results. Conclusions: Exposure to higher cumCVH can prevent the increase in baPWV and reduce the incidence of arterial stiffness. Highlights: Cumulative exposure to ideal CVH(cumCVH) had a significant inverse linear relationship with baPWV. The incidence of arterial stiffness decreased with higher cumCVH exposure levels. CumCVH is a practical index to monitor arterial stiffness.